University Students' Insights of Generative Artificial Intelligence (AI) Writing Tools - Al-Mothana M. Gasaymeh; Mohammad A. Beirat; Asma'a A. Abu Qbeita (MDPI AG, 2024)
The current study examined university students' insights into generative AI writing tools regarding their familiarity with, perceived concerns about, and perceived benefits of these tools in their academic work. The study used a cross-sectional descriptive research design, and data were collected using a questionnaire instrument. The participants were ninety-five undergraduate and graduate students from a College of Education at a university in Jordan. The results show that university students show moderate familiarity with generative AI writing tools (M = 3.14, SD = 0.81), especially in engagement but lacking technical knowledge. They also have moderate concerns (M = 3.35, SD = 0.85), particularly about misinformation and data security. Despite these concerns, students recognize the benefits (M = 3.62, SD = 0.81), especially regarding the capabilities of these tools in simulating creativity and fostering innovation. In addition, the results showed that gender and educational level appear to have little effect on familiarity, concerns, and perceived benefits regarding these tools. Based on the findings, the study recommends enhancing students' familiarity with generative AI tools through providing technical training, hands-on opportunities, and ethical discussions. In addition, the study recommends addressing students' concerns regarding generative AI writing tools by improving data security related to generative AI, providing ethical guidelines regarding the use of these tools, and boosting AI literacy. Finally, it is recommended to enhance students' perceptions of the benefits of generative AI writing tools by highlighting the creative potential of these tools within the educational setting, using these tools to offer personalized learning experiences that adapt to individual learning styles, and promoting collaboration through generative AI writing tools.